Digitalization in Islamic Family Law: an Opportunity or a Threat? - Khaiyyil Faizunan Nurun Nafi; Kamilatun Nisa'; Ahmad Taufiqur Rohman (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2024)
This study examines how Islamic family law can adapt to the modern era without losing its core values. It also provides recommendations for more adaptive laws in response to contemporary developments. The modern world has undergone many changes in various aspects of life, including Islamic family law, which is governed by Sharia principles. New challenges posed by technology include child custody and personal data protection, divorce through digital platforms, and the validity of online marriage documents. Moreover, the spread of false information on social media can potentially disrupt court proceedings. This study uses normative research to analyze Islamic family law issues in the digital era. The main data sources consist of legal literature, statutory regulations, and official documents related to Islamic family law. Data collection techniques were carried out using literature studies, where researchers looked at and analyzed various relevant articles, scientific works and legal sources. The analysis is carried out by identifying and categorizing the normative challenges that have emerged due to advances in digital technology and assessing how Islamic family law rules adapt to these changes. Islamic family law can adapt to the modern era without losing its core values by following an approach that focuses on two important aspects: flexibility of Islamic legal principles and contextualized reinterpretation of social changes. Some of the ways to achieve this are the Maqasid al-Shariah Approach, Ijtihad (Reinterpretation), Fiqh Minority (Fiqh al-Aqalliyat), the Role of the State in Legislation and the Enforcement of Human Rights in Islamic Family Law.